Venetoclax with high‐dose methotrexate and rituximab seem effective and well‐tolerated in the treatment of central nervous system involvement of chronic lymphocytic leukemia: A case report. Issue 2 (10th January 2020) - Beziat, Guillaume; Gauthier, Martin; Protin, Caroline; Oberic, Lucie; Lerebours, Fleur; Carlier, Jasmine; Ysebaert, Loïc
Abstract: Venetoclax with high‐dose methotrexate and rituximab seem effective and safe to treat central nervous system involvement of chronic lymphocytic leukemia. Abstract : Venetoclax with high‐dose methotrexate and rituximab seem effective and safe to treat central nervous system involvement of chronic lymphocytic leukemia.